2015
DOI: 10.5505/cayb.2015.43153
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion sting in pregnancy

Abstract: Scorpion Sting in Pregnancy ÖZETAkrep sokması sonrasında ha f yerel bulgulardan yaşamı tehdit edebilecek ağır sistemik bulgulara kadar değişebilen klinik seyir gözlenebilir. Bu olgu sunumumuzda, literatürde kısıtlı bilgiye sahip olduğumuz ve çocuk acillerde nadir karşılaştığımız akrep sokması sonrası çocuk acile başvuran bir gebede ve fetüste akrep toksininin etkilerini tartışmayı amaçladık. Olgumuz 17 yaşında 35 gestasyonel hafta+1 günlük gebe akrep sokması sonrasında acile başvurdu. Yerel bulgu dışında belir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…In many previous clinical cases described by Langley [25] , Guler et al [26] , Kamalak and Kosus [27] , Kaplanoglu and Helvaci [28] , Bozkurt et al [29] , Sarı et al [30] and Ozturk and Koca [31] , no adverse effect was reported in mothers or their fetuses after being stung by scorpion in different periods of pregnancy. Similarly, in a recent retrospective case series and literature review study, 24 pregnant women were admitted to the emergency department at Suruc (Sanliurfa) State Hospital due to scorpion stings and no important effects were reported on the fetus or the mother according to their medical records [11] .…”
Section: Discussionmentioning
confidence: 95%
“…In many previous clinical cases described by Langley [25] , Guler et al [26] , Kamalak and Kosus [27] , Kaplanoglu and Helvaci [28] , Bozkurt et al [29] , Sarı et al [30] and Ozturk and Koca [31] , no adverse effect was reported in mothers or their fetuses after being stung by scorpion in different periods of pregnancy. Similarly, in a recent retrospective case series and literature review study, 24 pregnant women were admitted to the emergency department at Suruc (Sanliurfa) State Hospital due to scorpion stings and no important effects were reported on the fetus or the mother according to their medical records [11] .…”
Section: Discussionmentioning
confidence: 95%